The effects of conductive nano fillers alignment on the dielectric properties of copolymer matrix - Md Habibur Rahaman; Usman Yaqoob; Hyeon Cheol Kim (Advanced Manufacturing: Polymer & Composites Science, 2019)
This research focuses on the improvement of the dielectric and energy harvesting properties of piezoelectric P(VDF-TrFE) copolymer matrix by the alignment of conductive reduced graphene oxide nano fillers. The dispersion and the morphology of the conductive nano fillers on the co-polymer matrix were characterized by scanning electron microscopy which showed a configurational phase transition due to highly conductive nano channel formation, steric hindrance, excluded volume interaction van-der-walls forces between adjacent reduced graphene oxide sheets. Five different piezoelectric nanocomposites were prepared by varying the reduced graphene oxide contents in P(VDF-TrFE) matrix to realize its optimum concentration in the matrix. From our analysis, we observed that, an optimized morphological structure plays a vital role in the formation of polar electroactive β phase on the co-polymer matrix through the good dispersion, filler alignment and interfacial interaction of reduced graphene oxide nano fillers. The as prepared nanocomposite film showed an enhanced crystallinity (50 ∼ 52%), dielectric constant (72 at 1 kHz), piezoelectric charge constant (−23 pC/N) with an output power of 3.2 µW at 1.8 MΩ load for 2 N mechanical force. All the outputs were observed without applying poling process. We expect that our synthesized self-poled nanocomposite can be a useful candidate for energy harvesting applications.